2005
DOI: 10.1002/jemt.20140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eupatorium adenophorum Spreng leaf extracts on the mustard aphid, Lipaphis erysimi Kalt: A scanning electron microscope study

Abstract: Scanning electron microscopic study revealed some remarkable adverse effects of Eupatorium adenophorum Spreng leaf extract on cuticular and antennal sensilla of the mustard aphid, Lipaphis erysimi Kalt. The study appears to be the first of its kind in providing evidence on toxic property of the plant on certain agricultural pests, although the indigenous tribes of the region know the insecticidal property of the plant for a long time. The study further provides indications regarding the neurotoxic nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Similarly, a set of three multiplets at δ 3.25, 1.63 and 1.52 and three singlets at δ 1.89, 1.82 and 1.78 were assigned to methane and methyl protons respectively. Its structure was further confirmed by 13 The 1 H-NMR spectrum of 2-acetyl-cadinan-3,6-diene-7-one (EA-5) exhibited characteristic peaks corresponding to cadinene skeleton. Some of the proton peaks were deshielded due to presence of neighboring carbonyl group at 7th position, acetyl group at 2nd position and double bond of cyclohexane ring (Table 2).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Similarly, a set of three multiplets at δ 3.25, 1.63 and 1.52 and three singlets at δ 1.89, 1.82 and 1.78 were assigned to methane and methyl protons respectively. Its structure was further confirmed by 13 The 1 H-NMR spectrum of 2-acetyl-cadinan-3,6-diene-7-one (EA-5) exhibited characteristic peaks corresponding to cadinene skeleton. Some of the proton peaks were deshielded due to presence of neighboring carbonyl group at 7th position, acetyl group at 2nd position and double bond of cyclohexane ring (Table 2).…”
Section: Resultsmentioning
confidence: 78%
“…Characteristic singlet at δ 2.12 was observed which may be assigned to acetyl group. The 13 Antifungal bioassay guided extraction revealed that hexane and EtOAc concentrates were the most active fraction (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have focused on the invasion and dissemination patterns of E. adenophorum, its physiological ecology, individual species biology characteristics, and prevention and utilization (Wang et al 1994;Dey et al 2005). The karyotype of E. adenophorum has also been characterized and was found to be 2n = 3x = 51, belonging to the ''2B'' type.…”
mentioning
confidence: 97%
“…The scanning electron microscopy has been proved to be versatile in assessing the effect of environmental stress, pollution, and toxic chemicals on surface morphology of various tissues in a number of animals (Dey et al, 2001(Dey et al, , 2005. The present study on SEM of the transverse section of the testes of the fishes collected from their natural habitat with acidic pH and also from adults raised in aquarium with acidic pH revealed some remarkable abnormal features.…”
Section: Resultsmentioning
confidence: 68%